Greenpreneur Desa: Membangun Ekonomi Berbasis Umkm Ramah Lingkungan - Rian, Arian Zikri; Yulistiyono, Agus (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The Community Service Program (KKN) in Talagasari Village was carried out as a form of community engagement focusing on strengthening Micro, Small, and Medium Enterprises (MSMEs) and improving the quality of education, health, social, and environmental aspects. The topic was chosen based on the village’s conditions, where local communities still face limitations in business management, digital literacy, and access to education and health information. The method of implementation included community needs assessment, participatory program planning, mentoring-based activities, and evaluation using both descriptive and qualitative approaches. The main program involved MSME empowerment through digitalization training, QRIS utilization, branding design, and inter-village collaborative seminars. Supporting programs included tutoring activities, elderly health services (posyandu), student medical check-ups, waste recycling into paving blocks, and participation in social and religious activities. The results show improved skills of MSME actors in utilizing digital platforms, increased motivation among children in learning, higher public awareness of health issues, and stronger social interaction within the community. This community service demonstrates that collaboration between students and local residents can foster positive changes in attitudes, socio-cultural dynamics, and economic empowerment. Therefore, the outcomes of the KKN program in Talagasari Village contribute significantly to building an independent, competitive, and sustainable community. Keywords: MSMEs; community empowerment; business digitalization; sustainable economy; community service